Study of Exhaustion of Direct Dyes under Optimized Conditions Spectrophotometrically - Naheed, Shazia; Ahmad, H.B.; Shahzad, Khurram; Abdullah, Muhammad; Zuber, Muhammad; Hussain, Mazhar (Asian Journal of Chemistry, 2011)
CI Direct blue 67 and CI direct red 81 were studied for optimization of conditions in exhaust dyeing process by varying different parameters like salt concentration, time, temperature and liquor ratio. Glauber's salt (Na2SO4·10H2O) or common salt (NaCl) is used as exhausting agent. The exhaustion of dye in dye bath was determined spectrophotometerically and its retention on fabric was tested on spectra flash (data colour 600). The dyeing results were evaluated by measuring colour yield, washing-fastness, rubbing-fastness and light-fastness. The best results were obtained when 4 g cotton fabric was dyed using 50 g/L Na2SO4·10H2O, at 95 ºC, for 1 h, in liquor ratio 1:10. After treatment, a fixer (Tino-fixer) was necessary for the best results.